Health x profit: who does win with a worksite health promotion program? - Glaycon Michels; Caroline de Oliveira Martins (Universidade Federal de Santa Catarina, 2001)
Even though many managers only invest in workers' health to increase their profi ts, countless employees have been improving their quality of life due to Workplace Health Promotion Programs (WHPP). This purpose of this article is to demonstrate the benefi ts to workers at the Universidade Federal de Santa Catarina achieved in the year 2000 with a WHPP. By means of a questionnaire, data were collected on compliance with workplace exercise breaks, wellbeing, changes to lifestyle and dissemination of knowledge that suggest that the quality of life of these workers improved in terms of less pain, better relationships, more physical activity and more stretching exercises and that what they learnt was lasting longer. RESUMO Mesmo que muitos empresários invistam na saúde do trabalhador somente para aumentar seus lucros, inúmeros empregados têm melhorado sua qualidade de vida devido a Programas de Promoção da Saúde do Trabalhador (PPST). Este artigo tem como objetivo relatar benefícios referentes à aplicação de um PPST em funcionários da reitoria da Universidade Federal de Santa Catarina, decorridos no ano 2000. Através da aplicação de um questionário, respostas condizentes à adesão à ginástica laboral, bem-estar, alteração do estilo de vida e difusão de conhecimento sugerem melhorias na qualidade de vida destes trabalhadores devido à diminuição de dores, melhor relacionamento, maior prática de exercício físico, mais alongamentos e maior vivência de ensinamentos.